Curriculum Change and Organizational Culture (Revista LIDER, 2020)
This article evaluates the impact of curriculum change for the Career of Midwifery, Faculty of Medicine at the Universidad de La Frontera, Chile, in the organizational culture, identifying its variables and their evolution. A qualitative, descriptive and exploratory research has been conducted by document analysis, Organizational Development group dynamics with the people involved, namely, academics, students and graduates. Academics and managers were asked to answer questionnaires and semi-structured interviews, who signed informed consents in order to become participants in this research. Group dynamics and questionnaires were analyzed by grouping the answers depending on their dimensions and frequencies, information which was validated and confirmed by interviews analyzed with the Atlas-ti 5.0 program. Curriculum innovation has meant a learning process where Career members have installed competencies related to self-learning, team-work and problemsolving among students; and, a facilitating role, tolerance and team work among academics.